Pattern of Doppler Ultrasonographic Scan Requests and Findings: A 3-Year Study - Olatunji AA; Odusan O (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2016)
Introduction: Doppler ultrasonography is a radiological investigative tool which is relatively new in developing countries, Nigeria inclusive. Objective: To describe the clinical indications, the pattern of requests and findings of Doppler ultrasonographic studies in a tertiary health facility in Sagamu, Nigeria. This is a preliminary report of a spanning June 2007 to July 2010 and highlighting the Methods: This initial report covered the period between June 2007 and July 2010. The subjects consisted of patients who were referred for Doppler Ultrasonography from public and private health facilities in Sagamu. The ultrasound scan was carried out using a Siemens's Sonoline G-40® Ultrasound Machine. The features recorded included the waveforms, peak velocities, pathologic features such as plaques, irregular pools of blood and the relative absence of flow as well as the lack of Doppler signals. Results: There were 42 patients comprising 29 (69%) males and 13 (31%) females, aged 16-78 years, with a mean age of 53 ± 15.5 years. The subjects were matched for age (p = 0.9). The clinical indications for Doppler ultrasound studies included Diabetes Foot Syndrome (DFS), Deep Venous Thrombosis (DVT), peripheral arterial disease, and leg swellings. Minor indications included oedema, gunshot wound, nephritic syndrome, supraclavicular tumour and varicose veins. The Doppler ultrasound findings were confirmatory of the clinical diagnosis of DVT in 5/8 (62.5%) and 5/23 (21.7%) in DFS patients. Conclusion: Doppler ultrasound confirmed a higher proportion of DVT compared to DFS.